Unlocking the Mysteries of Eating Disorders: A Life-Saving Guide to Your Child's Treatment and Recovery - B.Herzog David (MC Graw Hill, 2008)
This insightful and comforting guide, written by two internationally known experts, shatters the myths, mysteries, and misconceptions surrounding eating disorders. You will learn how to recognize EDs, identify causes, talk to your child, and find the best treatment. The book includes the widest range of professional care options available, both psychotherapeutic and medicinal, as well as preventive solutions for children who display early warning signs. Most inspiring of all are the real-life stories of families who have faced eating disorders--and triumphed.